Different cutoff points to diagnose low muscle mass and prediction of osteoporosis in postmenopausal women - Miranda, Camila; de Morais, Vinicius Faria Borges; Martins, Fernanda Maria; Pelet, Danyelle Cristina Silva; Orsatti, Cláudio Lera; Cangussu-Oliveira, Luciana Mendes; Petri Nahas, Eliana Aguiar [UNESP]; Santagnello, Samarita Beraldo; de Paula, Rodolfo Ferreira; Campos Souza, Markus Vinicius; Orsatti, Fábio Lera (Wolters Kluwer, 2021)
OBJECTIVE: This study aimed to verify which of the different cutoff points of low muscle mass (LMM) based on appendicular lean mass (ALM) is associated with osteoporosis in postmenopausal women (PMW). METHODS: Cross-sectional study. PMW (n = 355) were classified for the presence of osteoporosis (score <-2.5 standard deviations) at the femoral neck and lumbar spine and LMM (three cutoff points: ALM < 15 kg; ALM/height2 [ALM index] <5.67 kg/m2 and ratio between ALM and body mass index [ALMBMI] <0.512). RESULTS: After adjustments for confounding factors, binary logistic regression showed that ALM and ALM index were associated with osteoporosis at the lumbar spine (odds ratio [OR] = 5.3 [95% CI: 2.3-12.5] and OR = 2.5 [95% CI: 1.0-6.2], respectively) and only ALM was associated with osteoporosis at the femoral neck (OR = 16.1 [95% CI: 4.1-62.5]). When women were classified as having osteoporosis in at least one site, only ALM was associated with osteoporosis (OR = 7.7 [95% CI: 3.3-15.6]). There was no association between ALMBMI and osteoporosis. The predictive value of ALM for osteoporosis decreased after BMI or height were included as a covariate in the model. CONCLUSION: Absolute ALM (<15 kg) seems to be the most suitable for predicting osteoporosis based on LMM in PMW.